THE EFFECT OF IMMERSING BAY LEAF 25% ON THE MEAN SURFACE ROUGHNESS ACRYLIC RESIN TYPE HEAT - Saputera, Debby; Puspitasari, Dewi; Tedjohartoko, Andrew (FKG Unlam, 2017)
Background: Surface roughness is one of the factor which reduce the strength of dentures. Denture cleanser that can be used is chlorhexidine, however it may cause surface roughness acrylic resin type heat cured. Natural materials that can be used as a denture cleanser is Bay leaf. Bay leaf was known to have antibacterial and antifungal activity. Purpose: This research aims to analyze the effect of immersing extract bay leaf 25% for 5 days and 15 days compared with chlorhexidine gluconate 0.2% and aquades as denture cleanser. Method: This research is true experiment using post test-only with control group design. The sample used were forty-two samples, divided into six groups immersed in extract bay leaf 25%, chlorhexidine gluconate 0.2% and aquades for 5 days and 15 days. Surface roughness was measured using Surface Roughness Tester. Results: This research shows that the mean surface roughness of acrylic type heat cured soaked for 5 days and 15 days in extract bay leaf 25% (0,45 ± 0,019) and (0,55 ± 0,012), chlorhexidine gluconate 0.2% (0,53 ± 0,024) and (0,64 ± 0,012), aquades (0,37 ± 0,015) and (0,43 ± 0,013). The One-Way Anova test showed p=0,000 (p<0,05) that there was a meaningful difference on immersing extract bay leaf 25%, chlorhexidine gluconate 0.2% and aquades. Conclusion: Immersing bay leaf 25% has lower effect on surface roughness compared with chlorhexidine gluconate.